Effect on paternal supplementation of palm oil (Tocotrienol Rich Fraction) on male fertility / Noor Arshikin Talib - Talib, Noor Arshikin (2015)
Tocotrienol Rich fraction (TRF) is composed of tocotrienol isomer that is part of Vitamin E family. This study was performed to investigate the fertility potential and toxicity effects of TRF on male rats. Fifteen (15) adult male Wistar rats were randomly divided into 5 groups (n=3). Control negative groups was administered orally with distilled water (F), control positive group (G) groups were administered orally with tocopherol stripped com oil and TRF supplementation at dose of 30 mg/kg (H), 60 mg/kg(I) and 90 mg/kg(J). After 7 days of treatment, blood collection was performed by retro orbital sinus for biochemical analysis while sperm were collected from cauda epididymis for sperm analysis. 60 mg/kg showed the highest level of sperm count among TRF treatment group even though the positive control showed the highest sperm count among all groups. The results also showed normal sperm morphology were significantly increased in treated group (H-J) compared to negative/positive group. Hepatotoxicity assessment revealed significant decreased in ALP group in 30 mg/kg and 60 mg/kg of TRF treated group with control groups but no significant difference in AST, and ALT were found. Renal profile for nephrotoxicity of creatinine and urea level also showed no significant different. Reproductive hormone profile of FSH and LH showed significant difference however testosterone showed no significant different. Nevertheless, histological finding has revealed the improvement of spermatogenesis activity in 30 mg/kg and 60 mg/kg of TRF. This study was suggested that TRF have potential in improving fertility without significant hepatotoxicity and nephrotoxicity effect